2004
DOI: 10.1023/b:doop.0000036780.96560.74
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in electroretinograms and retinal morphology in rabbits treated with vigabatrin

Abstract: This study demonstrates changes in histopathology caused by vigabatrin in an animal model, which has not been reported previously. We have found that vigabatrin orally administrated to rabbits does not affect rod function but may reduce cone function in the full-field electroretinogram, which is similar to the previously reported vigabatrin effect on the human ERG. The results indicate that vigabatrin may damage or influence, at least one cell type in the rabbit retina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 14 publications
4
26
1
Order By: Relevance
“…We have previously found glial cell pathology in vigabatrin treated rabbits. 52 In the present study the histopathology results were similar showing in 4 of 6 treated rabbits a pathological immunohistology, mainly a severe accumulation of GABA in amacrine cells and in the inner plexiform layer. This was not seen in all treated rabbits, which may indicate that the reduced function precedes the immunohistochemical pathology.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We have previously found glial cell pathology in vigabatrin treated rabbits. 52 In the present study the histopathology results were similar showing in 4 of 6 treated rabbits a pathological immunohistology, mainly a severe accumulation of GABA in amacrine cells and in the inner plexiform layer. This was not seen in all treated rabbits, which may indicate that the reduced function precedes the immunohistochemical pathology.…”
Section: Discussionsupporting
confidence: 86%
“…58 In the present study we have demonstrated alterations in the full-field ERG in topiramate treated rabbits similar to the previously reported alterations in retinal function and morphology caused by vigabatrin. 52 These results indicate that topiramate may also have adverse effects on retinal function which in turn may cause visual field defects.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…GABA is an important modulatory neurotransmitter. A previous report has demonstrated that vigabatrin in rabbit retina causes changes in immunohistopathology characterized by an enhancement of the glial cells located in the peripheral parts of the retina, which may explain the concentric visual field defect found in patients taking the drug [14]. These changes in immunohistopathology were also correlated with a reduced cone b-wave amplitude in the rabbit full-field ERG, a result very similar to the reduced ERG in vigabatrin treated patients.…”
Section: Introductionsupporting
confidence: 52%
“…Full-field ERGs were recorded with a Nicolet analysis system (Nicolet Biomedical Instruments, Madison Wisconsin) as described previously [14]. The examinations were conducted according to the International Society for Clinical Electrophysiology of Vision (ISCEV) standards [26].…”
Section: Electrophysiologymentioning
confidence: 99%